Embedding Content and Language Integrated Learning (CLIL) into English for specific purposes curriculum for vocational high school - Hertati Mukadimah; Wening Sahayu (Jurnal Pendidikan Vokasi, 2021)
English is agreed upon as the standard language of communication throughout the world, including Indonesia. With this, teaching and learning English should be an integral part of the national education system in Indonesia because of the importance of English globally. One of the curricula in Indonesia that focuses on teaching English for Vocational High Schools (VHS) is English for Specific Purposes (ESP), where students learn English according to their needs and fields of interest. With the existence of this ESP as well as a variety of teaching methods and approaches, there is one approach that is considered truly effective in teaching this ESP program, namely the Content and Language Integrated Learning (CLIL) approach. This study aims to explore a set of literature to clarify the CLIL approach and determine if the evidence shows benefits in implementing the approach into the English for Specific Purposes (ESP) curriculum. The paper took a literature review approach and explored ten articles selected with specific criteria of being published within 2014-2020. The literature shows that the implementation of CLIL does have a positive output toward the teaching and learning process, especially for those who take English for specific purposes, such as in vocational high schools. The approach improves the linguistics aspects and the non-linguistic aspect or the students' soft skills, such as high order thinking skills, problem-solving, enhanced communication, intercultural awareness, and motivation in learning. However, to meet the success of the implementation of CLIL in the ESP curriculum, some considerations and special requirements are needed. The two distinctive preparation are the syllabus for the curriculum and the readiness of human resources; the teachers. Before applying the CLIL, the two factors mentioned need mechanisms that will support the success of CLIL for the ESP curriculum in vocational high schools. The writer proposes a model to be implemented if the curriculum for vocational high schools is going to apply CLIL. Yet, it needs more researches in the future to make sure whether the model works well or needs more improvements.